Differences in cyanophage and virioplankton production dynamics in eddies of opposite polarity in the North Pacific Subtropical Gyre - Weissenbach, Julia; Goldin, Svetlana; Hulata, Yotam; Lindell, Debbie (Frontiers in Marine Science, 2024)
Viruses are abundant in the ocean and influence both the composition of marine communities and biogeochemical cycles. Despite their high abundance, production rates of distinct virus taxa in the environment are largely unknown. Here, we investigated production dynamics of T4-like cyanophages and compared them to those of the total dsDNA virioplankton community in two adjacent eddies of opposite polarity in the North Pacific Subtropical Gyre. Virioplankton production rates were 3-fold higher in the cyclonic than in the anticyclonic eddy, potentially due to higher metabolic activity of their bacterial hosts in the cyclone, and had similar virus production rates during the day and night in the cyclone. In contrast, T4-like cyanophages had similar production rates in the two eddies but showed approximately 4-fold higher production rates at night than during the day, potentially due to a combination of greater infection, increased burst size and more cyanophages completing their infection cycle at night. These findings suggest that virioplankton community production is affected more by spatially differentiated environmental conditions while T4-like cyanophage production is more affected over the diel cycle. Differences in production for the T4-like cyanophages relative to the virioplankton community indicate that spatial variability at the mesoscale differentially impact distinct components of the virioplankton.